Lethal cardiac arrhythmia during central venous catheterization in a uremic patient: A case report and review of the literature. Issue 4 (6th March 2013) - Huang, Ya‐Chin; Huang, Jiun‐Chi; Chen, Szu‐Chia; Chang, Jer‐Ming; Chen, Hung‐Chun
Abstract: Double‐lumen central venous catheter (CVC) is a rapid access technique for hemodialysis (HD) when an arteriovenous fistula or graft is not available. A variety of procedure‐related complications have been reported, such as infection and pneumothorax, but serious cardiac complications are relatively less mentioned. We report a uremic woman with preexisting left bundle branch block who required emergent HD and received jugular double‐lumen CVC insertion, which was complicated by short‐duration ventricular tachycardia followed by complete atrio‐ventricular block and bradycardia. Pharmacological management did not reverse heart rate and rhythm. External pacing was not applied because she remained hemodynamically stable in the course of HD. Heart rate returned to sinus rhythm with left bundle branch block 4 hours later and did not recur through the whole admission period. We speculate that the transient arrhythmia might have been induced by mechanical contact with the ventricular wall during the procedure with the guided metallic wire. In conclusion, physicians responsible for CVC catheterization should pay more attention to patients with preexisting cardiac arrhythmia to prevent such technical mistakes from transpiring.